Pengembangan Bahan Ajar Berbasis Keterampilan Proses untuk Meningkatkan Hasil Belajar Siswa Materi Ekosistem pada Siswa Kelas V MI Nasyrul Ulum Bocek Karangploso Malang - Lathifah Abdiyah; Agus Mukti Wibowo (Jurnal Pendidikan Madrasah, 2021)
The development of teaching materials based on process skills in the ecosystem material is one of the teaching materials implemented to support and facilitate students in mastering the material in the learning process and can improve student learning outcomes. This study aims to (1) develop teaching material products based on ecosystem material process skills, (2) to develop textbooks that make students more interested in learning, and (3) to determine the improvement of student learning outcomes with material processing skills-based teaching ecosystem materials. The results of this study indicate that: (1) The product of this process skills-based teaching material is very feasible to be applied. It is evident from the results of the evaluation of the material expert validation test that the eligibility level is 100%, the design expert gets 83.75%, and the learning expert gets 93.75%, because the materials and designs used match the curriculum and student characteristics; (2) The level of attractiveness of process skills-based teaching materials in the field test was 92.77%, because the teaching materials were presented attractively and were designed by selecting images, colors, and fonts that were in accordance with the characteristics of the students; (3) The increase in student learning outcomes can be seen from the post-test results of the control class and the experimental class, the mean score of the experimental class is 83, on the other hand the average score of the control class is 53.82. The t-test results obtained = 11.562> = 2.00575. is rejected and is accepted, this shows that this teaching material makes students more familiar with the material, because practice questions are related to daily life and the student's environment, and are tested to improve student learning outcomes so that this process skills-based teaching material is suitable for use in learning in particular ecosystem matter. Pengembangan bahan ajar berbasis keterampilan proses materi ekosistem adalah salah satu bahan ajar yang diimplementasikan untuk menunjang serta mempermudah siswa dalam menguasai materi pada proses pembelajaran serta dapat meningkatkan hasil belajar siswa. Penelitian ini bertujuan untuk (1) mengembangkan produk bahan ajar berbasis keterampilan proses materi ekosistem, (2) untuk mengembangkan buku ajar yang membuat siswa menjadi lebih tertarik dalam pembelajaran, serta (3) untuk mengetahui peningkatan hasil belajar siswa dengan bahan ajar berbasis keterampilan proses materi ekosistem. Hasil penelitian ini menunjukkan jika: (1) Produk bahan ajar berbasis keterampilan proses ini sangat layak diaplikasikan. Terbukti dari hasil penilaian uji validasi ahli materi mendapat tingkat kelayakan 100%, ahli desain mendapat 83,75%, serta ahli pembelajar mendapat 93,75%, karena materi serta desain yang digunakan cocok dengan kurikulum serta karakteristik siswa; (2) Tingkat kemenarikan bahan ajar berbasis keterampilan proses pada uji lapangan didapat 92,77%, karna bahan ajar disajikan menarik serta didesain dengan pemilihan gambar, warna, serta jenis huruf yang sesuai dengan karakteristik siswa; (3) Peningkatan hasil belajar siswa terlihat dari hasil post-test kelas kontrol serta kelas eksperimen, nilai rata-rata kelas eksperimen adalah 83, sebaliknya nilai rata-rata kelas kontrol adalah 53,82. Hasil uji- t memperoleh = 11,562 > = 2,00575. Ho ditolak dan diterima, hal ini menunjukkan jika bahan ajar ini menjadikan siswa lebih menguasai materi, karena soal latihan berkaitan dengan kehidupan sehari-hari serta lingkungan siswa, serta teruji dapat meningkatkan hasil belajar siswa sehingga bahan ajar berbasis keterampilan proses ini layak digunakan dalam pembelajaran khususnya materi ekosistem.